2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9631072
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Balance Instability by Wearable Sensor Systems During Postural Transitions

Abstract: Several studies have demonstrated beneficial effects of real-time biofeedback for improving postural control. However, the application for daily activities, which also include postural transitions, is still limited. One crucial aspect is the time point of providing feedback, and thus its reliability. This might depend on the sensor system used, but also on how the threshold is defined.This study investigates which wearable sensor system and what kind of threshold is more reliable in a situation of a postural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For the first study, to trigger vibrotactile biofeedback, the threshold was defined as 1.2 times the absolute mean tilt angle assessed during baseline sway measurements for AP and ML (body sway-based threshold), respectively. In the second study, instead of a body sway-based threshold, we implemented a Limits-of-Stability-based threshold, as in a previous study, we have found this to better capture postural instability [51].…”
Section: Methodsmentioning
confidence: 99%
“…For the first study, to trigger vibrotactile biofeedback, the threshold was defined as 1.2 times the absolute mean tilt angle assessed during baseline sway measurements for AP and ML (body sway-based threshold), respectively. In the second study, instead of a body sway-based threshold, we implemented a Limits-of-Stability-based threshold, as in a previous study, we have found this to better capture postural instability [51].…”
Section: Methodsmentioning
confidence: 99%
“…Hessfeld et al explored examples of the wearable sensor system and type of threshold are more dependable in a postural shift scenario. Comparison of three sensing systems: pressure insoles system (IS), multiple inertial measurement unit systems (IMU), and a combination of both systems to provide reliable timing for potential biofeedback applied by a wearable device in daily activities [22]. Saboor et al discussed the two slashing technologies that are essential to contemporary gait analysis.…”
Section: Literature Reviewmentioning
confidence: 99%